Predictive durability of polyethylene terephthalate toward hydrolysis over large temperature and relative humidity ranges. (25th April 2018) - Dubelley, Florence; Planes, Emilie; Bas, Corine; Pons, Emmanuelle; Yrieix, Bernard; Flandin, Lionel
Abstract: The hydrolytic stability of poly(ethylene terephthalate) (PET) has already been largely reported. The chemical reactions induced by damp-heat exposure are well–known, and various kinetic expressions for the degradation have been presented. Using the data from previous studies, a new model for degradation is proposed. This model combines the effect of temperature and humidity in a single equation. Three parameters are utilized: the classical pair of activation energy ( Ea ) and pre-exponential factor ( f 0 ), and the reaction order ( n ) to the relative humidity ( RH ). The model may be used to fit the degradation data from various sources describing the hydrolysis over a large range of conditions (40–100 %RH, 60–160 °C). In addition a prediction of the crystallinity changes brought about by hydrolytic chain scission was performed. Prediction of useful lifetime in moist heat is also possible (hydrolysis of 0.2% ester moieties in the polymer). Graphical abstract: Image 1 Highlights: The Arrhenius law is extended to account for the detrimental effect of water. The model properly fits the data obtained from a large literature mining. The order of the hydrolytic reaction with respect to humidity is 1.5 A reasonable value is proposed for the activation energy of hydrolysis (100 kJ mol −1 ). A single master curve allows to predict the end-of-life for all PET morphologies.